La economía de los weblogs - Larrañaga Rubio, Julio (Estudios sobre el Mensaje Periodístico, 2007)
The blogosphere has experienced an incredible growth in the last few years. Comments and posts spread through blogs do affect substantially user’s behaviour in terms of purchase, both goods and services. Blogs phenomena has been popularized in Spain later than in other countries, but rapid growth of bloggers and awareness within an increasing audience guarantees the critical mass required for blogs to be a real and sustainable business supported on advertising. In addition, the market is ready. Forecast on advertising investment for the next few years allow high expectations on blogs economics.
Keywords: Weblogs; Information pricing; Meganiche; Blogs advertising; Blogs economics